Benefits of the nation with the implementation of the system of the only national account (2016)
The present test develop the "Sistema de Cuenta Única Nacional" is relation the management of entities resources Nation without situation of funds and own as well as the way that several state benefits are being produced including a set of entities which make transactions through this medium. Besides, it is clear that all the liquidity and investment resources of executing entities of Presupuesto General de la Nación